Flourishing dalam Perspektif Islam: Studi Fenomenologis pada Perawat Pasien Covid-19 - Gladis Corinna Marsha; Nina Zulida Situmorang; Ciptasari Prabawanti (Faculty of Ushuluddin and Humanities, 2022)
Covid-19 affects healthcare professionals like nurses who handle positive Covid-19 patients directly, potentially having both a physical and psychological impact. It is possible to adapt to a pandemic and still be able to thrive, despite the fact that the disease continues to endanger lives and alter daily life. In an Islamic perspective, flourishing is known as a gift from Allah SWT and can be viewed as a state in which all areas of a person's life perform exceptionally well and are able to reach maximal development so that they can function fully. This study uses qualitative methods and uses interviews as data collection and the findings show that the five subjects have prospered and attribute divine values to each of their occupations by viewing their labor as deserving of devotion. The five subjects have the capacity to learn wisdom and to express gratitude for the blessings Allah SWT has bestowed.